Analisis Persediaan Bahan Baku Usaha Tempe Risky Di Desa Serumbung Kabupaten Bengkulu Utara - Reni Astuti; Yun Fitriano; Sulisti Afriani (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The purpose of this study was to analyze the supply of raw materials for the Tempe Risky business in Serumbung Village, North Bengkulu Regency. The analytical method used is Economical Order Quantity (EOQ), Total Cost (TC), Re Order Point (ROP), and Safety Stock (SS). The results showed that to meet the need for raw material supplies of 336 sacks during the research period, from January 2021 to December 2021 (2021), the number of purchases that were Economical / EOQ of soybean raw materials had to be carried out by the Tempe Risky Business in Serumbung Village. North Bengkulu Regency is a total of 6 sacks per order with a frequency of 56 orders in one period from January 2021 to December 2021. Reordering or Re-Order Point (ROP) can also be determined, namely reordering should be done when the inventory is in warehouse as much as 4 sacks, with a lead time of 2 days so as not to hamper the company's production process. Total Cost can also be determined, namely the total cost of raw material inventory Rp. 55,456,650, - so that it can save on inventory costs of Rp. 163.643.350,- Safety Stock (SS) of 2 sacks that must be in the warehouse, this is intended so that there is no shortage of soybean raw materials if there is a delay in the delivery of raw materials.